Hexagon Fraud Analysis Using Beneish Ratio Index Method on Indonesia Healthcare Industry - Deniswara, Kevin; Mulyawan, Archie Nathanael; Prawira, Pieter (E-Jurnal Akuntansi, 2024)
The rapid growth of the industry requires governance to minimize the risks that may be detrimental to stakeholders due to the lack of security and monitoring that has caused fraudulent activity, especially in the healthcare industry. It has been proven by the identification of cases of fraud in health services, but it needs to be analyzed more deeply to find information that leads to changes in the presentation of financial statements, where this study adopted 7 variables of hexagon fraud on the health industry with calculations using beneish ratio index. The research adopted a quantitative method by obtaining data from the Indonesian Stock Exchange in the period 2016-2021, where there were 72 data of 12 companies that meeting the criteria of 24 companies. The results showed financial stability has an influence on fraudulent financial statements. However, the rest of the variables have no influence on fraudulent financial statements. Keywords: Healthcare industry; Fraud hexagon; Beneish ratio index; Financial statement fraud